Fatty Acid Desaturation during Chilling Acclimation Is One of the Factors Involved in Conferring Low-Temperature Tolerance to Young Tobacco Leaves. - Kodama, H. (1995)
The FAD7 gene, a gene for a chloroplast [omega]-3 fatty acid desaturase, is responsible for the trienoic fatty acid (TA) formation in leaf tissues. The TA content of the leaf tissue of the 25[deg]C-grown transgenic tobacco (Nicotiana tabacum cv SR1) plants, in which the FAD7 gene from Arabidopsis thaliana was overexpressed, increased uniformly by about 10%. Fatty acid unsaturation in all major leaf polar lipid species increased in the 25[deg]C-grown FAD7 transformants but was approximately the same between the control plants and the FAD7 transformants when grown at 15[deg]C. Therefore, the overexpression of the exogenous FAD7 gene leads to the same consequence in the tobacco plants as the low-temperature-induced TA production that may be catalyzed by an endogenous, temperature-regulated chloroplast [omega]-3 fatty acid desaturase. In the 25[deg]C-grown control plants, the chilling treatment caused symptoms of leaf chlorosis and suppression of leaf growth. The 25[deg]C-grown FAD7 transgenic plants conferred alleviation of these chilling-induced symptoms. A reductions of the chilling injury similar to that of the FAD7 transformants was also observed in the 15[deg]C-preincubated control plants. These results indicate that the increased TA production during chilling acclimation is one of the prerequisites for the normal leaf development at low, nonfreezing temperatures.